Bidirectional crosstalk between sleep disorders and gynecological cancers: unraveling molecular synergies and precision therapeutics - Mei, Hongxia; Zhao, Chenyu; Jin, Hongyu; Qi, Weiyi; Lu, Xiangqun; Xin, Yiqing; Wang, Wei; Sun, Yakai; Li, Wen-Yang (Frontiers in Medicine, 2025)
Sleep disorders, particularly obstructive sleep apnea (OSA), circadian disruption, and insomnia, are increasingly recognized as contributors to the onset and progression of gynecologic cancers. This review explores the bidirectional interactions between sleep dysfunction and malignancies such as ovarian, endometrial, and cervical cancers. Mechanistically, intermittent hypoxia (IH) from OSA promotes tumor aggressiveness through hypoxia-inducible factor-1 alpha (HIF-1α) stabilization, M2 macrophage polarization, and impaired DNA repair, while circadian disruption alters endocrine signaling and immune regulation. Disrupted sleep also perturbs the gut and vaginal microbiota, promoting systemic inflammation and tumor-supportive environments. Conversely, cancer therapies such as chemotherapy and radiotherapy exacerbate sleep dysfunction via neurotoxicity and fibrotic airway damage, especially in estrogen-deprived states. These interconnected mechanisms not only worsen clinical outcomes but also underscore sleep as a modifiable and actionable therapeutic target. Emerging integrative strategies—such as hypoxia-targeted nanomedicine, circadian-based chronotherapy, and microbiota modulation—offer promising avenues to enhance treatment efficacy and quality of life. Progress in this field hinges on interdisciplinary collaboration and the development of personalized care models that embed sleep health as a core component of gynecologic cancer management.